Efficiency in Microfinance Cooperatives - HARTARSKA, Valentina; NADOLNYAK, Denis; SHEN, Xuan (Revista Iberoamericana de Estudios de Desarrollo)
In recognition of cooperatives’ contribution to the socio-economic well-being of their participants, the United Nations has declared 2012 as the International Year of Cooperatives. Microfinance cooperatives make a large part of the microfinance industry. We study efficiency of microfinance cooperatives and provide estimates of the optimal size of such organizations. We employ the classical efficiency analysis consisting of estimating a system of equations and identify the optimal size of microfinance cooperatives in terms of their number of clients (outreach efficiency), as well as dollar value of lending and deposits (sustainability). We find that microfinance cooperatives have increasing returns to scale which means that the vast majority can lower cost if they become larger. We calculate that the optimal size is around $100 million in lending and half of that in deposits. We find less robust estimates in terms of reaching many clients with a range from 40,000 to 180,000 borrowers.